A review of the genus Potemnemus Thomson, 1864 (Coleoptera: Cerambycidae) with description of a new species from Papua New Guinea - Wallin, Henrik; Kvamme, Torstein (Zootaxa, 2015)
All preserved type specimens and type series of the genus Potemnemus Thomson, 1864 from museum collections have been examined. The presented taxonomic study is based on examination of morphological characters as well as studies of the genitalia. The genitalia are described for the first time. The type of P. scabrosus Olivier, 1790 is lost, and the original drawing has been designated as a lectotype. The monospecific genus Parapotemnemus Breuning, 1971 nov. syn. is considered to be a junior synonym of Potemnemus Thomson, 1864 based on similarities in both external and male genitalia characters. Potemnemus wheatcrofti (Breuning, 1971) nov. comb. thus becomes a new combination. The holotype of P. wheatcrofti nov. comb. is lost, and a paratype ♂ has been designated as a neotype. Potemnemus nylanderi nov. sp. is described from the eastern parts of Papua New Guinea. The following new synonyms within the genus Potemnemus have been introduced: P. hispidus Gressitt, 1952 nov. syn. is a junior synonym of P. sepicanus Kriesche, 1923, P. detzneri Kriesche, 1923 nov. syn. is a junior synonym of P. trimaculatus Lea, 1918, and P. loriai Breuning, 1956 nov. syn. and P. triturberculatus Breuning, 1942 nov. syn. are both junior synonyms of P. scabrosus (Olivier, 1790). As a result of the present study the following species have been resurrected to species level: Potemnemus trimaculatus Lea, 1918 sp. res., P. wolfi Berchmans, 1925 sp. res., and P. thomsoni Lansberge, 1880 sp. res. The genus Periaptodes Pascoe, 1866 gen. res. has been resurrected as a valid genus based on differences in both external and male genitalia characters, and re-descriptions of the genera Potemnemus and Periaptodes are presented. Consequently, the following species have been transferred back to Periaptodes from Potemnemus: Periaptodes frater (Van de Poll, 1887), P. lictor Pascoe, 1866, P. olivieri (Thomson, 1864), P. potemnemoides Kriesche, 1936. P. testator Pascoe, 1866, P. paratestator Breuning, 1980. P. testator has priority as the type species of the genus Periaptodes (designation by Breuning, 1944). McKeown’s designation in 1947 of Periaptodes lictor Pascoe, 1866 as type species of the genus is therefore invalid. A key to the species of Potemnemus is provided.